2021
DOI: 10.1155/2021/7611686
|View full text |Cite|
|
Sign up to set email alerts
|

Research on the Impact of mHealth Apps on the Primary Healthcare Professionals in Patient Care

Abstract: The goal of this study was to develop and use a questionnaire in order to analyse the effects of eHealth apps on patient care using Jordanian population. A two-stage cross-sectional research was conducted. A questionnaire was developed in the beginning to evaluate its consistency and legitimacy using Cronbach’s alpha coefficient, a multitrait connection atmosphere; the multivariate technique is component examination. In the study’s another phase, correlation and regression are used to determine the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Using mHealth was significantly associated with sub-optimal performance in the refugee settlement. This finding differed from previous studies that showed strong correlations between mHealth use and improved CHW performance by simplifying and reducing the workload [27,31,35,36]. These equivocal findings could be due to the refugee settlement operational settings and methodological discrepancies during analysis.…”
Section: Plos Global Public Healthcontrasting
confidence: 94%
See 1 more Smart Citation
“…Using mHealth was significantly associated with sub-optimal performance in the refugee settlement. This finding differed from previous studies that showed strong correlations between mHealth use and improved CHW performance by simplifying and reducing the workload [27,31,35,36]. These equivocal findings could be due to the refugee settlement operational settings and methodological discrepancies during analysis.…”
Section: Plos Global Public Healthcontrasting
confidence: 94%
“…mHealth is the use of mobile wireless technologies for public health surveillance and promotion [28]. Generally, studies on the adoption and advancements in mHealth show a positive correlation with improved healthcare practice and service delivery [29][30][31]. Similar correlations have been noted between mHealth and the performance of CHWs in low and middleincome countries.…”
Section: Introductionmentioning
confidence: 78%
“…While 92% of the adult population in the U.S. owned a mobile phone in 2015 [ 8 ], up to 97% had a mobile phone in 2021 [ 9 ]. Thereby, the use of mobile health (mHealth) apps has recently risen considerably to provide independent health care time and location [ 10 ]. Between 2014–2017, 235 new apps in the field of dermatology were registered representing a growth of 80.8% [ 11 ], while melanoma-related apps increased by 55.8% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applied Bionics and Biomechanics has retracted the article titled "Research on the Impact of mHealth Apps on the Primary Healthcare Professionals in Patient Care" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2] significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Applied Bionics and Biomechanics has retracted the article titled “Research on the Impact of mHealth Apps on the Primary Healthcare Professionals in Patient Care” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%